Penjamasan Pusaka Sunan kalijaga - Siti Muawanah (Analisa: Journal of Social Science and Religion, 2010)
This article discusses the washing ceremony of Sunan Kalijaga’s three heirlooms: Kyai Kutang Antakusuma, Kyai Crubuk and Kyai Sirikan, which is annually held by the ahli waris of Sunan Kalijaga in Kadilangu. This writing, however, is not intended to describe how the procession runs in details, but to convey the hidden messages of the ritual. There are at least three main meanings of the ritual. The first, the importance of the five daily prayers; the second,  familial  relationship among the ahli waris, and the last, economic benefit or profit motive.